2015
DOI: 10.1007/s11192-015-1661-z
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric dimensions of cryptographic research

Abstract: Information security has been a crucial issue in modern information management; thus cryptographic techniques have become inevitable to safeguard the digital information assets as well as to defend the invasion of privacy in modern information society, and likely to have far reaching impact on national security policies. This paper demonstrates the intellectual development of cryptographic research based on quantifiable characteristics of scholarly publications over a decade of the present century (2001 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Compared with previous cryptology research in which data from only a single reputable Western journal were collected and analyzed [ 24 ], the current study widened the international coverage using a broader data pool that covers all major journals in the field. Data for the present study were collected from Elsevier’s Scopus , one of the two major sources that aggregates international research journal publication metadata.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with previous cryptology research in which data from only a single reputable Western journal were collected and analyzed [ 24 ], the current study widened the international coverage using a broader data pool that covers all major journals in the field. Data for the present study were collected from Elsevier’s Scopus , one of the two major sources that aggregates international research journal publication metadata.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research performed by the present author identified a dramatic increase in information security research activity emanating from China [ 22 , 23 ]. Moreover, researchers using scientometrics have further narrowed the scope of analysis from the broader domain of information security to cryptology, which is an information security research specialty aimed at studying the making (cryptography) and breaking (cryptanalysis) of secure codes [ 24 ]. Moving to an even lower level of analysis, other researchers have applied scientometrics to the cryptology subspecialty, cryptography [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applied areas of research are prone to collaborative efforts. Quite often, the scholars are being forced to collaborate due to interdisciplinary agenda of research that requires knowledge across many fields (Pal, 2015 ). However, the positive impact on the citation of multi-authored publications has been promoting the growth of collaborations.…”
Section: Collaboration Scenariomentioning
confidence: 99%
“…Similarly, Coccia et al [34] conducted a scientometric analysis on publications and patents in quantum computing and quantum computers to identify the technological trajectories. Pal [35] analyzed an intellectual advancement and development in the field of cryptography through a quantitative study of literature published over the period 2001–2010. Gupta et al [6] presented an advancement in the domain of QC through qualitative and quantitative analysis of literature in the Scopus database (1992–2020).…”
Section: Literature Surveymentioning
confidence: 99%